1997
DOI: 10.1177/027112149701700207
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions Regarding the IFSP Process in a Statewide Interagency Service Coordination Program

Abstract: Development of an Individualized Family Service Plan (IFSP) for children receiving Part H services is an integral part of North Carolina's interagency Child Service Coordination Program. Perceptions of the IFSP process were assessed in a statewide survey of child service coordinators. Divergent viewpoints about the usefulness and process of devel-oping the IFSP emerged, depending on the program with which the child service coordinator worked. These findings have implications for training professionals about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Filla, Wolery, & Anthony, 1999;Strain, 1999;Warren, 1998). For example, studies have suggested that IFSPs still stress child outcomes to the exclusion of more broad-based family mediated outcomes and support strategies (Boone, McBride, Swann, Moore, & Drew, 1998;Bruder, Staff, & McMurrer-Kaminer, 1997;Farel, Shackelford, & Hurth, 1997;Summers et al, 1990); studies have also shown that service providers struggle with the delivery of services that include families (Filer & Mahoney, 1996;McBride & Peterson, 1997;McWilliam et al, 1995;McWilliam, Tocci, & Harbin, 1998). Additionally, both providers and researchers struggle with whether parent education and intervention on parent-infant interaction is encompassed within a family-centered framework (Mahoney et al, 1999;McCollum, 1999), whether early intervention should be child-centered or family-centered (Able- Boone, 1996, Beckman, Frank, & Newcomb, 1996, and whether the emphasis in early intervention should be relationship focused (Kelly & Barnard, 1999).…”
Section: Isaiahmentioning
confidence: 99%
“…Filla, Wolery, & Anthony, 1999;Strain, 1999;Warren, 1998). For example, studies have suggested that IFSPs still stress child outcomes to the exclusion of more broad-based family mediated outcomes and support strategies (Boone, McBride, Swann, Moore, & Drew, 1998;Bruder, Staff, & McMurrer-Kaminer, 1997;Farel, Shackelford, & Hurth, 1997;Summers et al, 1990); studies have also shown that service providers struggle with the delivery of services that include families (Filer & Mahoney, 1996;McBride & Peterson, 1997;McWilliam et al, 1995;McWilliam, Tocci, & Harbin, 1998). Additionally, both providers and researchers struggle with whether parent education and intervention on parent-infant interaction is encompassed within a family-centered framework (Mahoney et al, 1999;McCollum, 1999), whether early intervention should be child-centered or family-centered (Able- Boone, 1996, Beckman, Frank, & Newcomb, 1996, and whether the emphasis in early intervention should be relationship focused (Kelly & Barnard, 1999).…”
Section: Isaiahmentioning
confidence: 99%
“…Due to the multiple roles EHS staff play and need to assume, they need sufficient training and supervision with the IFSP process. Interdisciplinary and interagency training with EI staff together should be provided to ensure the implementation of Part C services for all young children who are served by multiple programs (Farel et al, 1997). For example, training and support provided to EHS staff working with EI by infant specialists from their regional Disabilities Services Quality Improvement Center helped service providers from EI and EHS to network and to brainstorm solutions to the problems they faced.…”
Section: Implications For Ehs Direct Service Providersmentioning
confidence: 99%
“…This study also provided evidence that scheduling difficulties, getting everyone 308 C. Zhang et al together and the use of at least two sets of documents for goal-setting across programs were the major challenges in coordinating services for dually enrolled children and families. As a result, lack of communication, inadequate information and confusion in the IFSP process often occur (Farel et al, 1997). Informal and formal structures need to be developed to facilitate staff awareness and understanding of the programs or agencies involved (Summers et al, 2001).…”
Section: Implications For Ehs Program Practices and Policymentioning
confidence: 99%
See 2 more Smart Citations